The wisdom of finance: discovering humanity in the world of risk and return - Desai, Mihir A. (Houghton Mifflin Harcourt, 2017)
The Harvard Business School professor draws upon literature, film, philosophy, and history to argue that, at the core of finance and financial practices, there is a place for principles, ethics, and humanity